Clinical significance of changes in the expression level of markers of surrogate breast cancer subtypes in recurrent and metastatic foci (literature review) - Yu. S. Krumin; V. A. Khaylenko; N. A. Kozlov; G. Yu. Cheremis; A. V. Petrovskyy; D. V. Khaylenko; E. V. Artamonova; E. I. Kovalenko (Опухоли женской репродуктивной системы, 2021)
The article analyzes data from the world literature for the period from 2005 to 2020 on the relationship between the variability of immunohistochemical expression of estrogen and progesterone receptors, HER2/neu protein and the index of proliferative activity in invasive breast cancer with the course of the disease and the response to medication.